Commitment, actions, and challenges on locally led climate change adaptation in Nepal - Popular Gentle; Jony Mainaly (Climate Risk Management)
Nepal has more than a decade of experience in formulating and implementing climate change policies, plans, frameworks, and institutional mechanisms for local adaptation. Drawing upon this experience, this research aims to elucidate the existing policies, institutional commitments and capacity that underpin local adaptation. Furthermore, it seeks to delineate the mechanism through which these commitments are translated into action fostering empowerment of poor and vulnerable communities for locally led adaptation (LLA). Our research involved a comprehensive review of major policies and legal and procedural documents related to climate change adaptation. We analyzed Local Adaptation Plans for Action (LAPA), carried out in-depth interviews with frontline actors and a participant observation and focus group discussions with LAPA communities. The research features that despite a strong policy commitment, adaptation in Nepal is struggling with institutional barriers, contested interest between key authorities, limited capacity, and unequal distribution of resources to support LLA. The LAPA analysis shows the priorities and investment plans are mostly intended to continue business as usual practices addressing bio-physical and natural hazards rather than properly understanding and addressing underlying, pre-existing, and structural causes of vulnerabilities. Notwithstanding the established evidence about differential impacts of climate change, the response mechanisms have exhibited limited realization of this knowledge. Future trajectory of LLA in Nepal hinges on the proactive efforts of the government to reform institutional and fund flow mechanisms, capacity, commitment, and a changing mindset for the devolution of decision making at the local level and making a substantial progress in climate financing.